EDUKASI TUBERKULOSIS (TB) KEPADA KADER PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) KELURAHAN DUREN SAWIT - Marta; Siti Aisyah; Fitri Savitri; Farida Tuahuns; Putri Eka Sari (Jurnal Bakti untuk Negeri, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycrobacterium Tuberculosis that enters the body through inhaling the droplets, such as saliva or phlegm as the media, containing pulmonary tuberculosis of the infected person. Based on the data from the Central Statistics Agency (BPS) in 2020, East Jakarta is the location with the most TB patients in the entire Jakarta with a total of 12,334 patients. As the most populous administrative city in the Special Capital Region of Jakarta, East Jakarta is resided by 28.76% or around 3.04 million people out of 10.56 million people residing in the entire province. The total population in 2019 in Duren Sawit District alone reached 399,595 people with a population density per square kilometer is of 17.64, that makes the area one of the districts with a high population density in the administrative area of East Jakarta. This is what motivated us to conduct TB education counseling to the Woman of Family Welfare Empowerment Program in Duren Sawit Village. Statistical tests show an increase of knowledge of the respondent after TB education was carried out. This increase in knowledge falls into the medium category. The highest increase occurred in the question number 10 related to the role of the family in preventing TB transmission.